﻿Intelectuais, modernidade e discurso educativo no Jornal “Diário dos Campos” (1907-1928). - Souza, Eliezer Felix de (2010)
This dissertation analyzes the response to the country’s debate on education in the Diário dos Campos newspaper, acknowledging the participation of Ponta Grossa intellectuals (Jacob Holzmann, Hugo Mendes de Borja Reis and José Cadilhe) in publicizing educational ideas. This analysis goes from 1907 to 1928, basing itself on fragments which were published in this newspaper in addition to the concept of the intellectual as an organizer of culture as discussed by Antonio Gramsci and in the interpretation of discourse in Bakhtin’s circle. This article discusses the role of intellectuals in the process of organizing and spreading a view of the world marked by the symbols of modern times and public education. Founded on documentation, it is possible to show that this group, in the newspaper, established a means of communication within the educational discussions promoted in the major cities of Brazil and reasserted education’s salvationist discourse to fight illiteracy and the social problems existing in the city of Ponta Grossa.